2011
DOI: 10.2466/06.11.13.15.pr0.109.6.896-906
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Exercise Behavior among Chinese Youth with Hearing Loss: A Randomized Controlled Trial Based on the Transtheoretical Model

Abstract: The transtheoretical model proposes that behavior change is experienced as a series of stages. Interventions tailored to these stages are most likely to be effective in progressing people through the model's hypothesized behavior change continuum. In this study, a stage-tailored, 12-week, exercise behavior intervention based on the transtheoretical model was conducted among a sample of 150 Chinese youth with hearing loss. Participants were randomized into an intervention or control group with all the core tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Stages of change in physical activity behavior in the intervention group, unlike the control group, improved significantly after three months of intervention. This result matches those of previous studies, which have reported that educational interventions based on the transtheoretical model can increase physical activity (1,9,10,(18)(19)(20)(21)(22)(23). However, Hutchison et al studied the interventions based on the transtheoretical model for changing physical activity behavior and showed that the model may not be the most appropriate for changing physical activity behavior.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Stages of change in physical activity behavior in the intervention group, unlike the control group, improved significantly after three months of intervention. This result matches those of previous studies, which have reported that educational interventions based on the transtheoretical model can increase physical activity (1,9,10,(18)(19)(20)(21)(22)(23). However, Hutchison et al studied the interventions based on the transtheoretical model for changing physical activity behavior and showed that the model may not be the most appropriate for changing physical activity behavior.…”
Section: Discussionsupporting
confidence: 65%
“…As with the control group, in the intervention group, perceived barriers did not decrease after the intervention although other studies have shown that an educational intervention based on transtheoretical model can decrease the perceived barriers significantly (1,18,20,21). The lack of decrease in perceived barriers can be attributed to the fact that some barriers could not be remedied by the educational intervention.…”
Section: Discussionmentioning
confidence: 56%
“…Exercise can modify our visual, auditory, and olfactory sensory perception by increasing blood flow or inducing other physical changes in the relevant brain regions (Delp et al., 2001; Krishnamurti and Grandjean, 2003; Davranche et al., 2005; Marioni et al., 2010; Si et al., 2011). Numerous studies have indicated that different exercise patterns have a positive effect on human sensory perception.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some criticisms about the model, in particular the idea that there are or might be discrete stages of change (Prochaska, 2006), studies have shown that intervention programs are more effective when they are tailored to a person's readiness for change using the stages of change continuum proposed in the TTM (Kosma et al, 2005;Kim & Cardinal, 2009;Si et al, 2011). However, there is limited research demonstrating the efficacy of this model or even its applicability among Iranian youth, although the model has shown promise in other youth samples (Cardinal et al, 1998;Suminski & Petosa, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%